Kristinuskoon viittaaminen eduskunnan täysistuntopuheenvuoroissa 1999–2019 - Äystö Tuomas (Teologinen julkaisuseura, 2026)
In this article, I analyze the speeches held in the Parliament of Finland between 1999 and 2019 that referenced Christianity (n = 622). I pay special attention to the ways in which the different parties construct Finnish society in relation to Christian notions, using qualitative and quantitative content analysis to classify the speeches as positive, neutral, or negative in their attitude towards Christianity. The results of this study show that references to Christianity are rare but mostly positive in tone. Proportionally, most references are found in speeches held by MPs belonging to the Christian Democrats, the Finns Party, and the Green League. I discuss these results in light of research from the political sciences, the sociology of religion and the study of religion, suggesting that it is useful to theorize the different societal visions found among the parties as sacred orders. This categorization draws attention to the fact that the largest gap in relation to religion in the Finnish parliament is not between the political right and left but between social liberals and conservatives, those who defend the particular sacred order they deem proper for society.